Digital Transformation of Woven MSMEs Traditional: Development Android Application –OpenCart for Online Marketing and Sales - Firdaus Annas; Nita Fitriani (Program Studi Bisnis Digital - Fakultas Ekonomi dan Bisnis Islam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the local economy, particularly in Lembah Melintang District, which is renowned for its traditional woven products. However, limitations in marketing and promotion remain major challenges for artisans to compete in wider markets. This study aims to design an Android-based application integrated with Opencart as a digital platform for promoting MSME woven products. The development employed a descriptive Research and Development (R&D) method through an iterative approach, involving user needs analysis, intuitive interface design, and the integration of e-commerce features. The findings reveal that the developed application successfully provides an interactive product catalog, online ordering system, digital payment methods, and user-friendly inventory management. The main contribution of this study lies in presenting a technological solution that not only enhances the visibility and accessibility of MSME products in the digital era but also strengthens the competitiveness of local artisans at the national level. The implementation of this Opencart-based application demonstrates that digital transformation can serve as an effective strategy to support the sustainability and market expansion of MSMEs rooted in local wisdom. UMKM (Usaha Mikro, Kecil, dan Menengah) memiliki peran strategis dalam mendukung perekonomian lokal, khususnya di Kecamatan Lembah Melintang yang dikenal dengan produk anyaman tradisional. Namun, keterbatasan dalam pemasaran dan promosi menjadi kendala utama bagi para pengrajin untuk menembus pasar yang lebih luas. Penelitian ini bertujuan merancang aplikasi berbasis Android dengan integrasi Opencart sebagai sarana promosi digital produk UMKM anyaman. Pengembangan dilakukan dengan metode Research and Development (R&D) secara deskriptif melalui pendekatan iteratif yang mencakup analisis kebutuhan pengguna, perancangan antarmuka intuitif, serta integrasi fitur e-commerce. Hasil penelitian menunjukkan bahwa aplikasi yang dikembangkan mampu menyediakan katalog produk interaktif, sistem pemesanan daring, metode pembayaran digital, serta manajemen inventaris yang mudah digunakan. Kontribusi utama penelitian ini adalah menghadirkan solusi teknologi yang tidak hanya meningkatkan visibilitas dan aksesibilitas produk UMKM di era digital, tetapi juga memperkuat daya saing pengrajin lokal hingga ke tingkat nasional. Implementasi aplikasi berbasis Opencart ini membuktikan bahwa transformasi digital dapat menjadi strategi efektif dalam mendukung keberlanjutan dan ekspansi pasar UMKM berbasis kearifan lokal.